Chemical- and radiation-induced haemorrhagic cystitis: current treatments and challenges - Payne, Heather (Blackwell Publishing Ltd, 2013)
To review the published data on predisposing risk factors for cancer treatment-induced haemorrhagic cystitis (HC) and the evidence for the different preventive and therapeutic measures that have been used in order to help clinicians optimally define and manage this potentially serious condition. Despite recognition that HC can be a significant complication of cancer treatment, there is currently a lack of UK-led guidelines available on how it should optimally be defined and managed. A systematic literature review was undertaken to evaluate the evidence for preventative measures and treatment options in the management of cancer treatment-induced HC. There is a wide range of reported incidence due to several factors including variability in study design and quality, the type of causal agent, the grading of bleeding, and discrepancies in definition criteria. The most frequently reported causal factors are radiotherapy to the pelvic area, where HC has been reported in up to 20% of patients, and treatment with cyclophosphamide and bacillus Calmette-Guérin, where the incidence has been reported as up to 30%. Mesna (2-mercaptoethane sodium sulphonate), hyperhydration and bladder irrigation have been the most frequently used prophylactic measures to prevent treatment-related cystitis, but are not always effective. Cranberry juice is widely cited as a preventative measure and sodium pentosanpolysulphate as a treatment, although the evidence for both is very limited. The best evidence exists for intravesical hyaluronic acid as an effective preventative and active treatment, and for hyperbaric oxygen as an equally effective treatment option. The lack of robust data and variability in treatment strategies used highlights the need for further research, as well as best practice guidance and consensus on the management of HC.